Postbiotic Sodium Butyrate Mitigates Hypertension and Kidney Dysfunction in Juvenile Rats Exposed to Microplastics - You-Lin Tain; Ying-Jui Lin; Chih-Yao Hou; Guo-Ping Chang-Chien; Shu-Fen Lin; Chien-Ning Hsu (Antioxidants)
Background: Plastic production has led to widespread microplastic (MP) pollution, with children more vulnerable to MPs than adults. However, the mechanisms linking MP exposure to hypertension and kidney disease in children remain unclear. This study explored whether sodium butyrate, a short-chain fatty acid (SCFA) with antioxidant and anti-inflammatory properties, could mitigate MP-induced hypertension and kidney damage in juvenile rats. Methods: Male Sprague-Dawley rats (3 weeks old) were randomly assigned to four groups (n = 8/group): control, low-dose MP (1 mg/L), high-dose MP (10 mg/L), and high-dose MP with sodium butyrate (400 mg/kg/day). Rats were euthanized at 12 weeks. Results: High-dose MP exposure impaired kidney function and increased blood pressure, which were alleviated by sodium butyrate through reduced oxidative stress, modulation of gut microbiota, increased plasma butyric acid levels, and enhanced renal SCFA-sensing G protein-coupled receptor 43 expression. Conclusions: Sodium butyrate holds potential for mitigating MP-induced hypertension by reducing oxidative stress, modulating the gut microbiota, and elevating butyric acid levels.